2022
DOI: 10.24235/al.ibtida.snj.v9i2.11888
|View full text |Cite
|
Sign up to set email alerts
|

Development of Digital Teaching Materials Based on Betawi Local Food to Increase Ecoliteracy in Elementary School Students

Abstract: Ecoliteracy is an awareness about the importance of saving the environment from potential hazards. Consuming local food is part of ecoliteracy which can be introduced through digital teaching materials. This research aims to produce such materials based on Betawi local food to increase ecoliteracy in elementary school students. The approach used was research and development involving 52 grade IV elementary school students from two different schools in East Jakarta for a smallscaled trial. Product validation wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Children are easily attracted and provoked into consuming advertised foods regardless of whether they are beneficial for the body (Fitriyah, 2015). Nutritional imbalances are often found in advertised instant foods such as noodles which are easily obtained by children (Mink et al, 2010;Norman et al, 2018;Stuart et al, 2020;Vioreza & Supriatna, 2020). An analysis from Korea National Health and Nutrition Examination Survey (KNHANES) III in 2005 regarding diet revealed that a person who consumes instant noodles has a high intake of energy, fat, sodium, but has a low intake of protein, calcium, phosphorus, iron, potassium, and vitamins, when compared to people who do not eat instant noodles (Park et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Children are easily attracted and provoked into consuming advertised foods regardless of whether they are beneficial for the body (Fitriyah, 2015). Nutritional imbalances are often found in advertised instant foods such as noodles which are easily obtained by children (Mink et al, 2010;Norman et al, 2018;Stuart et al, 2020;Vioreza & Supriatna, 2020). An analysis from Korea National Health and Nutrition Examination Survey (KNHANES) III in 2005 regarding diet revealed that a person who consumes instant noodles has a high intake of energy, fat, sodium, but has a low intake of protein, calcium, phosphorus, iron, potassium, and vitamins, when compared to people who do not eat instant noodles (Park et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Current education makes teachers provide meaningful, creative and innovative learning that utilizes technology. The use of technology in learning materials makes learning materials more interesting with a combination of the text, video, animation and so on that can be used anywhere and anytime (Juliarti, 2022;Khoiron et al, 2021;Vioreza et al, 2022). The innovation of technology-based teaching material can affect student learning outcomes so that there is an incrase in learning outcomes during the learning process (Papadakis et al, 2020;Setiyani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%